Challenges to the implementation and enforcement of socio-economic rights in Mozambique - Ampofo, K.K.K. (University of Pretoria, 2010)
A Dissertation submitted to the Faculty of Law University of Pretoria, in partial fulfilment of the requirements for the degree Masters of Law (LLM in Human Rights and Democratisation in Africa). Prepared under the supervision of K.K.K. Ampofo of the Faculty of Law, University of Ghana, Legon.